Implementation of Two Stay Two Stray (TSTS) Learning Model in Class X Islamic Education Learning at Insan Cendekia Mandiri Boarding School: Implementasi Model Pembelajaran Two Stay Two Stray (TSTS) dalam Pembelajaran PAI Kelas X di SMA Insan Cendekia Mandiri Boarding School - Nafi’ah, Adinda Mar’atun; Nadlif, Ainun (Indonesian Journal of Education Methods Development, 2020)
The implementation of the Two Stay Two Stray (TSTS) learning model in ICMBS High School has its own uniqueness in its application. Even the application of this learning model is in great demand by many students. Therefore this study aims to (1) find out the application of the Two Stay Two Stray (TSTS) learning model in PAI learning at ICMBS Sidoarjo High School, (2) find supporting and inhibiting factors in the application of Two Stay Two Stray (TSTS) learning models in learning PAI at ICMBS High School in Sidoarjo. The type of research used in this study is descriptive qualitative research. The results of the research are: (1) Implementation of the Two Stay Two Stray (TSTS) Learning Model applied has a difference with the implementation of the Two Stay Two Stray (TSTS) learning model in general. (2) Supporting factors include: pleasant class atmosphere, great motivation of students, learning media is quite easy and available, learning models are easy to understand The inhibiting factors for the implementation of the Two Stay Two Stray (TSTS) learning model include: (1) The level of ability of different students and (2) requires a long time and is less effective.